A compact hairpin filter with stepped hairpin defected ground structure - Sajjad, Hassan; Altaf, Ahsan; Khan, Sana; Jan, Latif (Institute of Electrical and Electronics Engineers Inc., 2018)
A compact hairpin line bandpass filter is presented with two different defected ground structures (DGS). The DGS are used to reduce the distributive response of the microstrip filter. The harmonic at 2 fo is suppressed to below -20 dB. The filter has an insertion loss (IL) greater than -3 dB and return loss (RL) of 26 dB at the center frequency, 2.4 GHz. The designed filter has a sharp roll-off and a wide band of operation. The filter is fabricated using RO4350 substrate and measured results are compared with the simulations.
Keywords: Bandpass Filter; Defected Ground Structures; Hairpin Filter; Insertion Loss